Odpowiedź:
Szczegółowe wyjaśnienie:
1. 4 bo [tex]2^4=16[/tex]
2. -4
bo [tex]3^{-4}=(\frac{1}{3})^4= \frac{1}{81}[/tex]
3. 3/2
oznaczmy sobie:
[tex]log_9 27 = x\\9^x = 27\\(3^2)^x= 3^3\\3^{2x}=3^3\\2x =3\\x=\frac{3}{2}[/tex]
4. [tex]log 10^7 - log_{0,5} 8 = 7 - (-3) = 10[/tex]
[tex]log_{0,5} 8 = -3 \\\text{bo } (\frac{1}{2})^{-3} = 2^3 = 8[/tex]
5.
[tex]2^{log_2 6}=6[/tex]
korzystamy tu z własności:
[tex]a^{log_a p}=p[/tex]
6.
[tex]4^{log_2 9} = 2^{2log_2 9} =2^{log_2 9^2}= 2^{log_2 81}=81[/tex]
Po drodze użyta własność:
[tex]nlog_a b = log_a b^n[/tex]